1986
DOI: 10.1152/jn.1986.56.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Encoding timing and intensity in the ventral cochlear nucleus of the cat

Abstract: Physiological response properties of neurons in the ventral cochlear nucleus have a variety of features that are substantially different from the stereotypical auditory nerve responses that serve as the principal source of activation for these neurons. These emergent features are the result of the varying distribution of auditory nerve inputs on the soma and dendrites of the various cell types within the nucleus; the intrinsic membrane characteristics of the various cell types causing different responses to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
356
1
3

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 354 publications
(386 citation statements)
references
References 0 publications
26
356
1
3
Order By: Relevance
“…The synchronization coefficient, calculated from the model PSTH, is 0.99. This is in good agreement with recorded synchronization coefficients of O I units (Rhode and Smith, 1986).…”
Section: Pure-tone Stimulisupporting
confidence: 91%
See 4 more Smart Citations
“…The synchronization coefficient, calculated from the model PSTH, is 0.99. This is in good agreement with recorded synchronization coefficients of O I units (Rhode and Smith, 1986).…”
Section: Pure-tone Stimulisupporting
confidence: 91%
“…Godfrey et al (1975) found that O I unit responses to pure-tone stimuli ( f > 2 kHz) reveal one sharply timed action potential at stimulus onset followed by no or little (<10 spikes/s) subsequent activity during the sustained portion of the tone. He concluded that these ideal onset responses that were confirmed in a number of subsequent studies (e.g., Rhode and Smith, 1986;Rhode, 1994) can be associated with octopus cell responses. In contrast to their onset response at high stimulus frequencies, O I units can entrain to low-frequency pure tones ( f < 800 Hz), where they emit exactly one spike at each stimulus cycle (e.g., Rhode and Smith, 1986), if the stimulus frequency is included in the cell's frequency-response area.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations